Pengaruh Literasi Keuangan, Gaya Hidup Hedonisme, dan Perencanaan Keuangan Terhadap Pengelolaan Keuangan Pribadi Mahasiswa Akuntansi UPN "Veteran" Jawa Timur - Ardy Ramadhan Feryanto; Sri Trisnaningsih (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The goal of this research was to ascertain how accounting students at UPN "Veteran" East Java handled their personal finances in relation to their level of financial literacy, hedonistic lifestyle, and financial planning. Quantitative methodology is employed. The participants in this research were East Java accounting students from the UPN "Veteran" classes of 2019 and 2020. 85 respondents were utilized as samples in this research, and they were selected using the purposive sampling approach and computed using the Slovin formula. The questionnaire approach using the Google form was used for the study's data gathering procedures. Structural Equation Modeling (SEM) is the data analysis method employed in this work, while SmartPLS 3.0 was used for data administration. (1) Financial literacy has an impact on the personal financial management of accounting students at UPN "Veteran" East Java, according to the study's findings. (2) The hedonistic way of living affects how UPN "Veteran" East Java accounting students handle their own finances. (3) Accounting students at UPN "Veteran" East Java's personal financial management is impacted by financial planning. Keywords: Financial literacy; Hedonism Lifestyle; Financial Planning